One-step synthesis of uniformly distributed SiOx–C composites as stable anodes for lithium-ion batteries. Issue 31 (25th July 2022) - Chen, Siyu; Xu, Yanan; Du, Hongbin
Abstract : Uniformly dispersed SiO x –C@CNT composites synthesized using a simple solution method exhibit excellent cycling stability. Abstract : SiO x is one of the most promising anode materials for lithium-ion batteries (LIBs), due to its high theoretical capacity and low cost. However, the huge volume expansion and low electron/ion diffusion rate hinder its further commercial applications. Herein, a simple molecular polymerization method is developed to synthesize N, P co-doped SiO x –C composites (denoted as SiO x –C@CNT), in which SiO x and carbon are uniformly dispersed at the atomic level, and the embedded carbon nanotubes improve the lithium ion diffusion kinetics. Benefiting from the unique structure, the SiO x –C@CNT composites exhibit a high reversible capacity of 848 mA h g −1 at 0.1 A g −1 and long cycling stability (84.0% capacity retention after 1500 cycles). More impressively, the LiCoO2 ∥SiO x –C@CNT full battery also exhibits stable cycle life (only 4.7% capacity loss after 300 cycles at 1 C). These results show the application potential of the SiO x –C@CNT anode in LIBs.